Students Holistic Character Development At Sekolah Menengah Kejuruan in Tualang Siak District - Risdayati , Risdayati; Elfis, Rozian (Green Publisher Indonesia, 2022)
Sekolah Menengah Kejuruan (SMK) is equivalent with School Sekolah Menengah Atas (SMA). It is one of the receptacle demand types of knowledge that more emphasize expertise or vocational. The age of student is teenagers and behavior as average teenager. Teenager is a very vulnerable age and still look for teak self as well as easy affected by things negative. At SMKN1 Tualang it also happened same thing with behavior teenager generally and very easy affected with negative things. For that will done construction character student the in determine his future. This coaching started with the initial survey about students’ character, who finally grouped into the three group, i.e group students who do not problem, group problem student light and student with level problem high. Students’ collaboration with several parties is carried out in fostering students and fostering the education system itself, namely libraries, the role of the principal, the role of Guidance Counseling Teachers. It is hoped that this holistic development will be able to direct the role of schools in fostering their students.